The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1051/0004-6361/201014582
|View full text |Cite
|
Sign up to set email alerts
|

The CHESS spectral survey of star forming regions: Peering into the protostellar shock L1157-B1

Abstract: We present the first results of the unbiased survey of the L1157-B1 bow shock, obtained with HIFI in the framework of the key program Chemical HErschel Survey of Star forming regions (CHESS). The L1157 outflow is driven by a low-mass Class 0 protostar and is considered the prototype of the so-called chemically active outflows. The bright blue-shifted bow shock B1 is the ideal laboratory for studying the link between the hot (∼1000-2000 K) component traced by H 2 IR-emission and the cold (∼10-20 K) swept-up mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(61 citation statements)
references
References 22 publications
5
56
0
Order By: Relevance
“…Of course, the relevance of this observation of W33 A to conditions in L1157 B1 is open to question. As we shall see in Section 3, the intensity of the 572 GHz line of ortho-NH 3 -observed in L1157 B1 by means of Herschel/HIFI (Codella et al 2010) -suggests that the initial abundance of NH 3 ice is much less than the observations of W33 A would imply; a similar conclusion is reached in the case of CH 3 OH.…”
Section: Chemistrymentioning
confidence: 59%
See 2 more Smart Citations
“…Of course, the relevance of this observation of W33 A to conditions in L1157 B1 is open to question. As we shall see in Section 3, the intensity of the 572 GHz line of ortho-NH 3 -observed in L1157 B1 by means of Herschel/HIFI (Codella et al 2010) -suggests that the initial abundance of NH 3 ice is much less than the observations of W33 A would imply; a similar conclusion is reached in the case of CH 3 OH.…”
Section: Chemistrymentioning
confidence: 59%
“…2. Also shown in this figure are the intensity of the J = 5 → 4 transition, observed with the Herschel/HIFI instrument (Codella et al 2010), and the intensities of the J = 3 → 2 and J = 6 → 5 lines, reported by Lefloch et al (2010), which were derived from Caltech Submillimeter Observatory (CSO) observations and smoothed to the 39 arcsec diameter of the HIFI band 1b beam. The line intensities predicted by the CJ-type model are also plotted.…”
Section: Co Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the Spitzer data, the recent millimeter and submillimeter spectral line observations of outflows and jets from ground (e.g., Tafalla et al 2010;Santiago-García et al 2009) and from Herschel (e.g., Codella et al 2010;Lefloch et al 2010) will offer new clues to the nature of the EHV gas and its relation to the lowvelocity outflow shells. Though a few selected outflows have been well studied in H 2 emission using all H 2 pure rotational lines from S(0) to S(7) with IRS (e.g., Neufeld et al 2006;Nisini et al 2010), the IRAC images available in the Spitzer archives have the potential to study the H 2 emission in a large sample of outflow sources.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The range of relevant temperatures is very broad, from 5 K up to 2500 K, and the role of scattering partner (quencher) is played by the interstellar background gasses, mostly He and H 2 , but also by H 2 O in cometary comas. Usually, calculations of inelastic cross sections 12 are carried out using quantum scattering codes such as MOLSCAT.…”
Section: Introductionmentioning
confidence: 99%